Removal of methylene blue dye by solvothermally reduced graphene oxide: a metal-free adsorption and photodegradation method - Siong, Valerie Ling Er; Lee, Kian Mun; Juan, Joon Ching; Lai, Chin Wei; Tai, Xin Hong; Khe, Cheng Seong (Royal Society of Chemistry, 2019)
In this work, reduced graphene oxide (rGO) was fabricated at different reduction temperatures via an environmentally friendly solvothermal approach. The rGO formed at 160 °C clearly showed the partial restoration of the sp2 hybridization brought about by the elimination of oxygenated functionalities from the surface. Owing to the augmented surface area and the band gap reduction, rGO-160 exhibited the best adsorption (29.26%) and photocatalytic activity (32.68%) towards the removal of MB dye. The effects of catalyst loading, initial concentration of dye, light intensity, and initial pH of solution were evaluated. It was demonstrated that rGO-160 could achieve a higher adsorptive removal (87.39%) and photocatalytic degradation (98.57%) of MB dye when 60 mg of catalyst, 50 ppm of dye at pH 11, and 60 W m-2 of UV-C light source were used. The MB photodegradation activity of rGO-160 displayed no obvious decrease after five successive cycles. This study provides a potential metal-free adsorbent-cum-photocatalyst for the decontamination of dyes from wastewater. This journal is © The Royal Society of Chemistry.